Effort-reward imbalance and well-being among psychiatric nurses: the mediating role of burnout and decent work - Xiaoyan Zhang; Liya Zhang; Bowen Xue; Yanping Li; Mengmeng Yan; Hong Luo; Xiaoyu Huang (BMC, 2024)
Abstract Background Psychiatric nurses face additional challenges due to negative perceptions, workplace violence, and a lack of respect, impacting their well-being and job satisfaction, which are crucial for improving psychiatric care and patient outcomes. Objectives This study aims to examine the relationship between effort-reward imbalance, well-being, burnout, and decent work among psychiatric nurses. Methods This study used a cross-sectional design. Data were collected using a convenience sampling method in February 2024 from 397 psychiatric nurses at two psychiatric hospitals in Hangzhou and Huzhou, Zhejiang Province. The Effort-Reward Imbalance Scale, Decent Work Perception Scale, Maslach Burnout Inventory-General Survey, and General Well-Being Schedule Scale were used for data collection. Data analysis was conducted using SPSS 26.0 and the PROCESS macro. Results The study found that effort-reward imbalance among psychiatric nurses was negatively correlated with decent work (r = -0.564, p < 0.001) and well-being (r = -0.541, p < 0.001), and positively correlated with burnout (r = 0.603, p < 0.001). Burnout mediated the relationship between effort-reward imbalance and well-being (95% CI [-0.386, -0.257]), while decent work also served as a mediator (95% CI [-0.100, -0.012]). Additionally, burnout and decent work were found to mediate the relationship between effort-reward imbalance and well-being (95% CI [-0.050, -0.006]). Conclusion This study highlights the impact of effort-reward imbalance on well-being, confirming that burnout and decent work serve as mediators. Enhancing support, fair compensation, reasonable work schedules, and professional development can promote psychiatric nurses' perception of decent work and improve their well-being.